2019
DOI: 10.22175/mmb2018.10.0034
|View full text |Cite
|
Sign up to set email alerts
|

A Nutritional Survey of Commercially Available Grass-Finished Beef

Abstract: Consumer interest in the source of their food, its environmental footprint, and the impact of diet on health has supported the growth of the grass-finished beef (GFB) industry. Studies have concluded that GFB has distinct nutritional differences from conventionally-finished beef. As the GFB industry continues to expand, it is vital to continue to explore the nutritional complexities and variation in the product. To achieve this, a survey of grass-finishing production systems throughout the USA was conducted, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 30 publications
0
41
2
Order By: Relevance
“…Producer comparisons of beef cattle by region, finishing diets and age at harvest are summarized in Table 1. Producers are related to a previous study by Bronkema et al and the producer numbers match those in that study [7]. The cattle age at harvest for all four producers ranged between 23 and 28 months.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…Producer comparisons of beef cattle by region, finishing diets and age at harvest are summarized in Table 1. Producers are related to a previous study by Bronkema et al and the producer numbers match those in that study [7]. The cattle age at harvest for all four producers ranged between 23 and 28 months.…”
Section: Resultsmentioning
confidence: 74%
“…Previous research from our group demonstrated that GFB nutritional content varies significantly by producer/production system [7]. Variations in mean total n-6 and n-3 FAs contributed to a 20-fold range in observed n-6 to n-3 ratios (1.80 to 28.3) with some reported ratios much higher than previously suggested for GFB.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations